Pressure-induced novel nitrogen-rich aluminum nitrides: AlN6, Al2N7 and AlN7 with polymeric nitrogen chains and rings. Issue 21 (24th May 2021) - Du, Huifang; Ge, Yanfeng; Zhu, Jinlong; Guo, Wei; Yao, Yugui
Abstract : DFT calculations and the structural search method based on the particle swarm optimization (PSO) algorithm under pressure have been used to predict novel nitrogen-rich aluminum nitrides with polymeric nitrogen chains and rings. Abstract : Pressure-induced non-molecular phases of polymeric nitrogen have potential applications in the field of energetic materials. Here, through a structural search method combined with first-principles calculations, we have predicted four novel nitrogen-rich aluminum nitrides C 2/ m -AlN6, Cm -Al2 N7, C 2-Al2 N7 and P 1-AlN7 . Nitrogen atoms polymerize into infinite chains in C 2/ m -AlN6, C 2-Al2 N7 and P 1-AlN7 structures and form N3 chains and N4 rings in Cm -Al2 N7 . C 2/ m -AlN6 is stable in the pressure range from 30 to 80 GPa and Cm -Al2 N7, C 2-Al2 N7 and P 1-AlN7 are metastable in the pressure ranges of 35–65, 65–80 and 41–80 GPa, respectively. The present study predicts that C 2/ m -AlN6 has a superconducting transition temperature of 18.9 K at 0 GPa and can be quenched and recovered under ambient conditions. The energy densities of C 2/ m -AlN6, Cm -Al2 N7, C 2-Al2 N7 and P 1-AlN7 compounds are expected to be 4.80, 4.59, 5.46 and 5.59 kJ g −1, respectively, due to their high nitrogen content, indicating that they have potential to be high-energy density materials. The calculated Vickers hardness of C 2/ m -AlN6, Cm -Al2 N7, Cm -Al2 N7 and P 1-AlN7 is 43.86, 39.32, 63.96 and 33.58 GPa, respectively, showing that the novel nitrogen-rich aluminum nitrides are potential superhard materials as well. This study may encourage further experimental exploration of high N content superhard or high-energy density nitrides.